A MANET ROUTING PROTOCOL FOR IOT BASED ON LINK STABILITY, BANDWIDTH, ENERGY AND TRUST - P. Yuvaraja; Dr. P. Suganthi (International Engineering Journal For Research & Development, 2024)
The Mobile Ad hoc Networks (MANETs) is defined as a wireless mobile node system that has dynamic and self-organizing network topologies and does not require communication infrastructure. Routing is a key challenge in ad hoc networks because of its characteristics, such as the absence of centralized authority and temporary topology. In MANET, it is quite vital to take into account the battery capacity of the nodes and link stability at the same time. A lot of research has been done nowadays for network lifespan prolongation as well as energy efficiency. Along with the establishment of several routes between a source node and a destination node, the multipath routing algorithm also spreads the traffic load along various routes. In a specific path, it is able to diminish the congestion of traffic. Hence, route resilience whilst ensuring data transmission reliability is offered by multipath routing algorithms. This work has proposed a multipath routing scheme which is based on Ad hoc On-demand Multipath Distance Vector Routing (AOMDV) Protocol through utilizing Evolutionary Algorithms (EA) and the FireFly (FF) algorithm. This powerful routing scheme is capable of detecting efficient solutions for the MANET routing problem. The proposed FF-AOMDV is a probabilistic metaheuristic algorithm that is also capable of the quality-aware best path routing. The FF-AOMDV’s simulation outcomes demonstrate its superior performance over EA-AOMDV, AODV, and AOMDV.